Top motor and non-motor complaints in patients with Parkinson's disease - Baizabal-Carvallo, José Fidel; Alonso-Juarez, Marlene; Fekete, Robert (Frontiers in Aging Neuroscience, 2025)
BackgroundParkinson's disease (PD) is characterized by several motor and non-motor manifestations. These variable neurological complaints have diverse intensity and cause various degrees of disability.Objective methodsWe aimed to assess the top three most troublesome neurological complaints in patients with PD and correlated them with demographic and clinical variables, including the cognitive status assessed by the Montreal Cognitive Assessment (MoCA). Patients were asked about their three most troublesome neurological complaints after reviewing all motor and non-motor symptoms. Responses were divided into three tiers.ResultsWe studied 230 consecutive patients with PD. There were 130 (56.5%) male patients, with the mean age at evaluation of 67.7 ± 11.06 years. The most common neurological complaints in the top tier were (1) tremor (n = 80, 34.8%), (2) gait problems (n = 37, 16.1%), and (3) dyskinesia (n = 17, 7.4%). Speech difficulties, dyskinesia, and insomnia became more prominent 5 or 10 years after disease onset. A total of 159 (69.1%) patients reported “at least one non-motor symptom” among their top-3 tier complaints. Pain (n = 29, 12.6%), anxiety (n = 25, 10.8%), and insomnia (n = 25, 10.8%) were the most common non-motor symptoms. The presence of non-motor symptoms in the top three tiers was associated with decreased cognitive status (MoCA <25 points), but not with age, sex, or disease evolution time. Cognitive impairment was a significant predictor of non-motor symptoms in their top three tiers [odds ratio [OR]: 3.88 (95% CI: 1.647 to 9.169)]. Cluster analysis of patients with at least one non-motor symptom identified four groups: male or female patients with short evolution time, a postural-instability gait difficulty (PIGD) phenotype, and a dyskinetic group. The latter two were associated with a higher frequency of fatigue, insomnia, pain, and anxiety.ConclusionOverall, tremor was the most troublesome symptom in patients with PD, though high variability was observed. Approximately 69% of patients had at least one non-motor symptom among their top-3 complaints, which was associated with abnormal cognitive status. Speech difficulties, dyskinesia, and insomnia became more prominent with disease progression. Among patients with non-motor symptoms in the top three tiers, those with a PIGD phenotype or prominent dyskinesia exhibited a higher frequency of fatigue, insomnia, pain, and anxiety, suggesting a clustering effect of non-motor symptoms with these motor presentations.